SISTEM PEMUTUS TEGANGAN YANG KURANG UNTUK PENGAMANAN BATERAI DAN BEBAN DC MENGGUNAKAN ARDUINO NANO - Maruto Swatara Loegimin; Yoice Putung; Hasnira Hasnira; Sukandar Sawidin; Muchdar Dg. Patabo; Samsu Tuwongkesong; Marcel Lengkong (MBI, 2025)
Electrical control capacity or quality control capacity in electrical systems has always been very vital. However, the main attention should be focused on the characteristics of the supply voltage, especially in the modern era. A major constraint in the electrical structure is low voltage. Low voltage is a source of disturbance in the electrical system that affects the agility of related electrical equipment and can shorten the life of equipment, including battery components in DC energy systems such as solar panels. To anticipate the situation, low voltage circuit breaker hardware is used to protect batteries and DC devices from low voltage conditions, using a potentiometer as a voltage regulator, IC 7809 as a battery input voltage reducer, a switch to disconnect the battery, a power source, and a voltage display on the LCD screen and microcontroller control using Arduino Nano. The strategy applied can be a growth strategy or a research and development strategy. This approach is the foundation for planning and building the Moo voltage circuit breaker to protect batteries and DC devices. In the voltage test, Moo was able to disconnect the DC battery with ±99.795% accuracy. Standard tests for low voltage circuit breakers at 12 V and 24 V showed a difference of ±0.096 V and an error of ±0.554%.